Percutaneous epiphysiodesis using transphyseal screws for limb-length discrepancies: High variability among growth predictor models. (October 2015) - Monier, Bryan C.; Aronsson, David D.; Sun, Michael
Purpose: Percutaneous epiphysiodesis using transphyseal screws (PETS) was developed as a minimally invasive outpatient procedure to address limb-length discrepancy (LLD) that allowed immediate postoperative weight bearing and was potentially reversible by removing the screws. The aims of our study were to report our results using PETS for LLD and evaluate the accuracy of three growth predictor models. Methods: Sixteen patients with an average age of 14 years were treated for LLD using PETS. Thirteen patients had screws inserted in a parallel fashion and 3 had crossed screws. We compared the predicted LLD at skeletal maturity using the three growth predictor methods with the actual LLD at skeletal maturity and preoperative LLD with the final LLD at skeletal maturity. Results: The mean LLD at skeletal maturity between the predicted and final measurements was 0.2 cm using the Green−Anderson method, 1.4 cm using the Moseley method, and −0.1 cm using the Paley method. The mean preoperative LLD of 3.1 cm was corrected to 1.7 cm at skeletal maturity ( p < 0.001). Six patients complained of pain over the screw heads; however, no patient developed an infection or angular deformity. Conclusions: The three growth predictor methods predicted the final LLD within an average of 1.4 cm, but there was high variability. Although PETS improved the LLD by a mean of 1.4 cm, we believe the results would have been better if PETS was performed at an earlier skeletal age.